Optimized design to robotic production: integrating multipoint forming and free form material deposition in the mass customization of double curved facades. (18th December 2017) - Abdelmohsen, Sherif; Tarabishy, Sherif
Abstract: The mass customization of double curved façade panels is still in its infancy, in spite of recent efforts in panel manufacturing techniques. As these techniques have typically developed workarounds for curved façade manufacturing, they present challenges regarding economic feasibility, façade surface continuity, accuracy and waste reduction. We present an optimized design-to-robotic production approach that integrates multipoint forming and adjustable moulds together with robotic free form material deposition to produce mass customizable double curved façade panels. We argue that our approach generates customizable panels with complex geometry, and optimizes fabrication workflow, with minimum waster and maximum accuracy in representing irregular forms. Abstract : Overview of the proposed optimized design-to-robotic production workflow: (a) design of panel to be fabricated, (b) flexible mechanical modular system and silicone sheet to interpolate surface curvature from underlying modules, (c) tool paths generated from the digital model normal to the underlying base surface, (d) robotic arm deposits material over the modular system, (e) low polygon preview of the material deposition based on the tool paths of the robotic arm.